Research scope and collaboration opportunities in the world of orthodontics - Abu Bakar, Noraini (2017)
Orthodontics is a branch of dentistry that is concerned with facial growth, development of the dentition and occlusion, as well as with the diagnosis, interception and treatment of occlusal anomalies; popularly known as braces treatment.The objective of this talk is to introduce the speciality of orthodontics and to expose research areas that can potentially be carried out and to invite possible future collaboration. Some past and current research will be briefly discussed to offer better understanding on alliance.